2020
DOI: 10.3389/fphar.2020.558474
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: A Prospective Alternative for the Treatment of Chronic Pain

Abstract: Metformin (biguanide) is a drug widely used for the treatment of type 2 diabetes. This drug has been used for 60 years as a highly effective antihyperglycemic agent. The search for the mechanism of action of metformin has produced an enormous amount of research to explain its effects on gluconeogenesis, protein metabolism, fatty acid oxidation, oxidative stress, glucose uptake, autophagy and pain, among others. It was only up the end of the 1990s and beginning of this century that some of its mechanisms were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 222 publications
(260 reference statements)
1
19
0
1
Order By: Relevance
“…Interestingly, research data confirmed the efficacy of metformin in obtaining chronic pain relief [8].…”
Section: Brain Morphometric Studies: a Decrease In Grey Matter Volumementioning
confidence: 85%
“…Interestingly, research data confirmed the efficacy of metformin in obtaining chronic pain relief [8].…”
Section: Brain Morphometric Studies: a Decrease In Grey Matter Volumementioning
confidence: 85%
“…The liver is the center of human material and energy metabolism and the most important organ for glucose metabolism. For glucose metabolism, the liver is the center of hepatic glycogen synthesis and gluconeogenesis, and glucose uptake mediated by GLUT1 is essential for this process (82)(83)(84)(85)(86)(87)(88)(89). At the same time, HCC is derived from normal liver cells, and HCC not only has more vigorous material and energy metabolism, but also has the characteristics of aerobic glycolysis and Warburg (47).…”
Section: Discussionmentioning
confidence: 99%
“…Given that this drug is a disease-modifying agent in type II diabetes mellitus, it is possible that it has similar properties for reducing pain and its comorbidities 11 . Metformin has been shown to alleviate pain-like behaviors by activating the AMP-activated protein kinase (AMPK) and opioidergic pathways 6 , 12 . In rodent models of pain, metformin was found to inhibit peripheral and central inflammation, major contributing factors of pain progression, along with reflexive and non-reflexive pain behaviors 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%